BOOK REVIEW: Simion Retegan, ‟Luptând pe două fronturi. Memorandistul Vasile Lucaciu” [Fighting on Two Fronts. Vasile Lucaciu, the Memorandist], Argonaut Publishing House, Cluj-Napoca, 2016, 553 p. - CÂRJA, Ion (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2017)
Father Vasile Lucaciu, the Lion of Şişeşti, is indisputably one of the exceptional personalities of the Romanian nation's modern period. He contributed decisively to the developments of the national movement of Transylvanian Romanians during the decades prior to World War I, to the strengthening of the Romanian Greek-Catholic Church and, last but not least, to the preparation and accomplishment of the Great Union. Therefore, such a historical figure has triggered the appreciation of those who admired and loved him, but also the hatred of those who detested him during his lifetime. He was not forgotten by historians; today, a century after the events that fulfilled his efforts, he still represents a fresh, interesting, and generous study subject. Thus, 100 years after the Romanian battalions crossed the Carpathians, the Cluj-based historian Simion Retegan publishes a monograph dedicated to Vasile Lucaciu, a contribution that, according to current research on this topic, proves itself to be the most complete and voluminous work in respect of the proposed documentary contribution.